'Tu es déjà rentré?' Trauma, narcissism and melancholy in François Ozon's Sous le sable (2000). Issue 3 (2nd September 2017) - Ealy, Nicholas
Abstract: This article on François Ozon's Sous le sable (2000) examines how the disappearance of the main character's husband results in her fascination with his image (a ghostly returning figure) fixating her in a zone between loss and acceptance. Using this figure of the image, residing in a liminal zone between existence and non-existence, the author illustrates the ways in which it upsets traditional binary notions of time (past/present), reality (truth/fiction) and memory (remembrance/forgetfulness). To help in this endeavour, the author employs three distinct albeit interconnected theoretical discourses: (1) trauma as temporal liminality where past and present come together; (2) narcissism as the liminality of an image's realistic and fictitious natures; and (3) melancholy as that liminal space between a memory's retention and loss.